The interpretation of sergei rachmaninoff case study: moments musicaux op.16 no.4 by sergei Rachmaninoff / Wan Marissa Ali Mat - Ali Mat, Wan Marissa (2010)
The purpose of this research study is to extend the infonnation of the interpretation as a pianist based on Sergei Rachmaninoff's piano works and his philosophy. For the purpose of this fundamental research topic, I have focused towards interpretation analysis based on Sergei Rachmaninoff's Piano works: Moments Musicaux Op.16 No.4., which were composed as an etude study and at the same time require a musical perfection. Rachmaninoff was one of the perfonner in late romantic era. He also was a Russian composer, conductor and virtuoso pianist in his day.